2018
DOI: 10.1155/2018/9409121
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Encephalitis following Tandem Autologous Hematopoietic Stem Cell Transplantation: A Case Report and Review of the Literature

Abstract: Infection with Toxoplasma gondii is a rare but often fatal complication in hematopoietic stem cell transplantation (HSCT) recipients. Most cases have been reported in allogeneic (allo-) HSCT recipients, with only narrative reports following autologous HSCT (ASCT). We report the case of a 58-year-old Caucasian male presenting with toxoplasma encephalitis following tandem ASCT for myeloma and successfully treated with diagnosis by polymerase chain reaction analysis of cerebrospinal fluid. He was treated with sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Toxoplasmosis occurs mainly among allogeneic HSCT; however, rare cases are also reported among autologous-HSCT recipients, particularly with certain types of autologous HSCT (eg, tandem-repeat) associated with increased immunosuppresion. 13,14 Only a limited number of studies (n = 32) reported separately Toxoplasma infections and Toxoplasma disease cases. In 2 cohorts, the reported rate of Toxoplasma infection cases among all HSCT recipients was almost double the rate of Toxoplasma disease cases.…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasmosis occurs mainly among allogeneic HSCT; however, rare cases are also reported among autologous-HSCT recipients, particularly with certain types of autologous HSCT (eg, tandem-repeat) associated with increased immunosuppresion. 13,14 Only a limited number of studies (n = 32) reported separately Toxoplasma infections and Toxoplasma disease cases. In 2 cohorts, the reported rate of Toxoplasma infection cases among all HSCT recipients was almost double the rate of Toxoplasma disease cases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, despite the availability of prophylactic and treatment options, the reactivation of chronic toxoplasmosis still occurs and can become life threatening [4,[46][47][48]. In immunocompromised patients, the reactivation of chronic toxoplasmosis is due to various factors impairing the protective cellular immune response such as HIV infection, immunosuppressive therapies administered in the context of hematopoietic stem cell transplantation, solid organ transplant, or chemotherapy against cancer [30,[49][50][51][52][53][54]. In HIV patients, toxoplasmic encephalitis is the predominant manifestation of the disease, while pulmonary or disseminated toxoplasmosis is more characteristic of transplant patients [2,55].…”
Section: Toxoplasmosis In Immunocompromised Patientsmentioning
confidence: 99%
“…The aforementioned treatment modalities spare chronic toxoplasmosis and target only the acute form of the infection [48,[57][58][59]. Reactivation of tissue cysts, which are the hallmark of chronic toxoplasmosis, occurs when the host immunity is suppressed [18,[29][30][31][32][33][34]. For instance, in HIV patients an association between CD4 counts and T. gondii-related neurologic symptoms was reported [27].…”
Section: Pyrimethaminementioning
confidence: 99%
“…Immunosuppression triggers the reactivation of chronic toxoplasmosis, leading to serious complications and potential fatality [1,[26][27][28]. Reactivation was mostly documented in HIV patients or patients treated with immunosuppressive therapies prior to solid organ or hematopoietic stem cell transplantation [18,[29][30][31][32][33][34][35]. Indeed, among solid organ transplanted patients, orthotopic heart transplant recipients presented with the highest risk of reactivation of toxoplasmosis, owing to the high propensity of T. gondii cysts in striated muscles [36].…”
Section: Introductionmentioning
confidence: 99%